Online measurement of mean residence time of supercritical-pressure fluid with/without chemical reaction in pipe flow: A particle image statistics method considering optical distortion and radial uneven distribution of tracer particles. (31st August 2022) - Wang, Yusen; Cheng, Yuxiang; Li, Minghao; Jiang, Peixue; Zhu, Yinhai
Highlights: New nonintrusive, in-situ method for the visualization and measurement of MRT. Consideration of optical distortion caused by drastic changes in the fluid properties. Two optical arrangements were proposed and compared. Correcting uneven radial distortion of the tracer particles for NOA. Accurate measurement of MRT at pyrolysis reaction conditions. Abstract: This paper proposed a nonintrusive, in-situ experimental method for visualizing and measuring the mean residence time (MRT) of supercritical-pressure pipe flow with/without chemical reactions based on the high-frequency sampling of laser-induced particle images. Normal and oblique optical arrangements (NOA & OOA) for the incident laser were applied to induce particle scattering in the JP-10 pipe flow, using SiO2 microsphere as tracers. Optical distortion caused by drastic change in fluid properties was analyzed. The relative deviation of the proposed particle image statistics (PIS) method was within ±4% with NOA after considering optical distortion and uneven radial distribution of particles. Although the same level of accuracy was achieved with OOA without the need for correction, the noise in images became significant when the fuel approached pseudo-critical temperature. When there was no influence from pyrolysis, the MRT simulated using 1D subroutine agreed well with measured data. However, the relative deviation increased after pyrolysis.